Pelatihan Digital Marketing Dan Pengemasan Produk Frozen Food dalam Upaya Memperluas Pasar dan Meningkatkan UMKM Desa Kedunglumpang - M. Qoyum Zuhriawan; Purbowo Purbowo; Malichatuz Zahro (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2024)
Technological progress is something that cannot be avoided in today's life, because technological progress will run in line with scientific progress. Every innovation is created to provide positive benefits, provide many conveniences, and as a new way of carrying out activities for human life. Especially in the field of technology, society has enjoyed the many benefits brought by the innovations that have been produced in the last decade. Therefore, current technological advances must be utilized for economic needs, one of which is to market superior products from UMKM. Apart from that, to support marketing, training is provided for product packaging to make it more attractive. So the potential for product sales will be greater. The result of this service is that people can package products more attractively, and are able to market products through digital channels